Evaluating Facility Infrastructure for Prevention of Mother-to-Child Transmission of HIV—A 2015 Assessment of Major Delivery Hospitals in Atlanta, Georgia. (6th July 2018) - Smith, Somer L; Chahroudi, Ann M; Camacho-Gonzalez, Andres F; Gillespie, Scott; Wynn, Bridget A; Badell, Martina L; Swartzendruber, Andrea; Hazra, Rohan; Wortley, Pascale; Chakraborty, Rana
Abstract: Objective: Our goal was to evaluate the infrastructure of programs for the prevention of mother-to-child transmission (PMTCT) of human immunodeficiency virus (HIV) in major delivery units in the Atlanta, Georgia, metropolitan statistical area and to assess the knowledge, attitude, and practice of providers in these facilities around PMTCT. Methods: Hospital assessments and individual knowledge and practices were surveyed among 71 healthcare providers from March 2015 to March 2016 in 11 hospitals that deliver 40000 infants annually, which represents 70% of all deliveries in the Atlanta metropolitan statistical area. Included were questions about HIV testing for mother–infant pairs, test result turnaround times, policies and procedures for PMTCT, opt-out versus opt-in testing, availability of rapid point-of-care testing on labor and delivery units, and postnatal prophylaxis. Results: Seventy-three percent (8 of 11) of the hospitals had limitations in their PMTCT infrastructure, and 36% (4 of 11) reported no standardized policies for care of HIV-infected women. Three labor and delivery units used opt-in HIV testing of women. Only 27% (3 of 11) of the hospitals reported nucleic acid testing of HIV-exposed infants. Oral zidovudine for infant prophylaxis was available in all the hospitals, but 64% (7 of 11) of them did not stock nevirapine. Fifty-nine percent (24 of 44) of the obstetricians did not routinely offer rapid testing at delivery without a third-trimester HIV test, and 78% (n = 32 of 41) of them did not offer testing at delivery if the woman declined antenatal testing. The facility with the most annual births in Georgia did not offer rapid testing at delivery for women with an unknown HIV status. Conclusion: We identified several limitations in PMTCT infrastructure that might have contributed to perinatal HIV transmissions. The need to address these healthcare gaps to eliminate mother-to-child transmission of HIV in the United States is urgent.